TRADISI PERAYAAN KEMATIAN DI DESA BATU KE’DE: STUDI TENTANG NILAI SOSIAL DAN RELIGIUS DALAM ADAT MASYARAKAT ENREKANG - Aldi Trisno Nur; Muh. Aidil; Indri Alfianingsih (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2025)
Death celebration is one of the traditional processions that must be carried out in the community. The obligation to carry out the death celebration is because this celebration is included in the customs entrenched in several regions that are still thick with customs. Adat is a rule of life that although not promulgated by the ruler, is herniated and obeyed by the people with the belief that these rules apply as a law, meaning that as one of the customs in various regions, such as in Batu Ke'de Village, Enrekang Regency. The community is obliged to celebrate the celebration. This is because custom is a regulation that must be respected and obeyed by the community as a guideline for acting and behaving.